Chemokine receptor patterns in lymphocytes mirror metastatic spreading in melanoma - Jacquelot, Nicolas; Blattner, Carolin; Umansky, Viktor (The journal of clinical investigation, 2016)
Melanoma prognosis is dictated by tumor-infiltrating lymphocytes, the migratory and functional behavior of which is guided by chemokine or cytokine gradients. Here, we retrospectively analyzed the expression patterns of 9 homing receptors (CCR/CXCR) in naive and memory CD4+ and CD8+ T lymphocytes in 57 patients with metastatic melanoma (MMel) with various sites of metastases to evaluate whether T cell CCR/CXCR expression correlates with intratumoral accumulation, metastatic progression, and/or overall survival (OS). Homing receptor expression on lymphocytes strongly correlated with MMel dissemination. Loss of CCR6 or CXCR3, but not cutaneous lymphocyte antigen (CLA), on circulating T cell subsets was associated with skin or lymph node metastases, loss of CXCR4, CXCR5, and CCR9 corresponded with lung involvement, and a rise in CCR10 or CD103 was associated with widespread dissemination. High frequencies of CD8+CCR9+ naive T cells correlated with prolonged OS, while neutralizing the CCR9/CCL25 axis in mice stimulated tumor progression. The expansion of CLA-expressing effector memory CD8+ T cells in response to a single administration of CTLA4 blockade predicted disease control at 3 months in 47 patients with MMel. Thus, specific CCR/CXCR expression patterns on circulating T lymphocytes may guide potential diagnostic and therapeutic approaches.